The role of the Sufi orders in supporting the Ottoman rule in Algeria between the 16th-18th centuries - saadali, amani; nafti, ouafia (The Algerian Historical Journal, 2026)
The Suffi Orders had occupied an important place in the Algerian Society, as it had a significant role in several events prior to the Ottoman presence, which made it as one of their main pillars in establishing their ruling in the country and preserve its continuity for three centuries, because of their spiritual position and their alliance with the Ottomans in Jihad in Algeria. The aim of this study is to show the effectiveness of their policy and the reaction of the Algerian Suffis to it, focusing on the political role the Suffi orders had played by highlighting the extent of Suffism position and their contribution to the support of the Ottoman governance in Algeria, which resulted in a specific strategy played by the Ottoman governors towards the Suffi orders that eventually gained them major successfull policy results.